2017
DOI: 10.1016/j.jaim.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kunapa jala and Pancha gavya on plant quality, physiology, biochemistry, yield and growth attributes – A case study of Withania somnifera Dun.

Abstract: Background‘Vrikshayurveda’, an ancient science of plant life described by Surapala, has clearly outlined a systematized agricultural practice that insisted on the use of Kunapa jala (KJ) and Pancha gavya (PG) to enhance the yield and quality of plants.ObjectiveAn experiment was conducted to evaluate the effect of KJ and PG on growth, physiological, biochemical, quality attributes and yield of Withania somnifera Dun.Materials and methodsThe effect of KJ and PG was evaluated in comparison with control, organic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…The application of organic liquid manures significantly enhanced the plant growth parameters due to the better and rapid availability of essential plant nutrients. Kunapajala application enhanced the growth attributes and these observations are in lines with the report of Brajeshwar, (2002), Mishra (2007), Deshmukh et al (2012), Ali et al (2012), Sarkar et al (2013) and Ankad et al (2017). Increased plant height might be due to increased uptake of nutrients.…”
Section: Resultssupporting
confidence: 88%
“…The application of organic liquid manures significantly enhanced the plant growth parameters due to the better and rapid availability of essential plant nutrients. Kunapajala application enhanced the growth attributes and these observations are in lines with the report of Brajeshwar, (2002), Mishra (2007), Deshmukh et al (2012), Ali et al (2012), Sarkar et al (2013) and Ankad et al (2017). Increased plant height might be due to increased uptake of nutrients.…”
Section: Resultssupporting
confidence: 88%
“…10% Kunapajala led to early germination due to increased αamylase activity, resulting in accelerated growth and flowering. These findings align with previous studies on ashwagandha and gladiolus, indicating Kunapajala's efficacy in improving vegetative parameters (Ankad et al, 2017;Tamrakar et al, 2018) [2,22] . Fermented fertilizers containing active phenolic compounds, which potentially inhibit oxidase activity and increasing the tenacity of IAA in plants, enhancing the florets number per spike in gladiolus (Sankari et al, 2015) [20] .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a study conducted by Kumbar et al (2016) highlighted the positive effect of jeevamrit application on the increased yield and yield-attributing characteristics of French beans. Similarly, Ankad et al (2017) found similar results in Withania somnifera, where kunapajala treatments resulted in higher leaf area index, and total leaf area, chlorophyll a, b, and carotenoids.In contrast, soil application of farmyard manure showed lower yield attributes compared to the various doses of liquid manures. This finding is consistent with the results of Swain et al (2015), who demonstrated that plant height, the number of branches, and yield can be increased by applying a bio-enhancer at intervals of 10 days in chili crops.…”
Section: Resultssupporting
confidence: 66%